High‐Pressure Synthesis of a Nitrogen‐Rich Inclusion Compound ReN8⋅x N2 with Conjugated Polymeric Nitrogen Chains. Issue 29 (19th June 2018) - Bykov, Maxim; Bykova, Elena; Koemets, Egor; Fedotenko, Timofey; Aprilis, Georgios; Glazyrin, Konstantin; Liermann, Hanns‐Peter; Ponomareva, Alena V.; Tidholm, Johan; Tasnádi, Ferenc; Abrikosov, Igor A.; Dubrovinskaia, Natalia; et al.
Abstract: A nitrogen‐rich compound, ReN8 ⋅x N2, was synthesized by a direct reaction between rhenium and nitrogen at high pressure and high temperature in a laser‐heated diamond anvil cell. Single‐crystal X‐ray diffraction revealed that the crystal structure, which is based on the ReN8 framework, has rectangular‐shaped channels that accommodate nitrogen molecules. Thus, despite a very high synthesis pressure, exceeding 100 GPa, ReN8 ⋅x N2 is an inclusion compound. The amount of trapped nitrogen (x) depends on the synthesis conditions. The polydiazenediyl chains [−N=N−]∞ that constitute the framework have not been previously observed in any compound. Ab initio calculations on ReN8 ⋅x N2 provide strong support for the experimental results and conclusions. Abstract : A nitrogen‐rich compound, ReN8 ⋅x N2, was synthesized by a direct reaction between rhenium and nitrogen at high pressure and temperature. The crystal structure has rectangular‐shaped channels that accommodate nitrogen molecules. The amount of trapped nitrogen (x) depends on the synthesis conditions. The polydiazenediyl chains [−N=N−]∞ that constitute the framework have not been previously observed in any compound.